2016
DOI: 10.4238/gmr.15038389
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP1A1 (cytochrome P450) MspI polymorphism in women with endometriosis

Abstract: ABSTRACT. Endometriosis is a disease that affects 10 to 15% of the women of reproductive age. It is characterized by the presence of endometrial-like tissues outside of the uterus. Some definitions claim that the functional ectopic tissue is sensitive to the action of hormones. Severity of endometriosis is defined according to a system proposed by the American Society for Reproductive Medicine, which is based on laparoscopic findings. A large number of genetic polymorphisms has been reported for CYP1A1, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
1
Order By: Relevance
“…The case-control study with the smaller sample size investigated the T > C change. 115 Four Asian studies also investigated this base pair change, but found no association. 72,105,[116][117][118][119] No association with migraine was found.…”
Section: Esr2 Genementioning
confidence: 99%
“…The case-control study with the smaller sample size investigated the T > C change. 115 Four Asian studies also investigated this base pair change, but found no association. 72,105,[116][117][118][119] No association with migraine was found.…”
Section: Esr2 Genementioning
confidence: 99%
“…A mutação de genes também está associada à infertilidade na endometriose. Alguns dos principais genes polimórficos que podem aumentar o risco de desenvolvimento de endometriose compreendem a interleucinas (MATALLIOTAKIS et al, 2018;ZHAO et al, 2018), arilamina N-acetiltransferase 2 (NAT2) (FAYEZ et al, 2018), CYP1A1 (BARBOSA et al, 2016;MOURA, 2016b), p53 (DE MORAIS et al, 2016, p. 53;SANTOS et al, 2018;MOURA, 2016b) e eNOS (SANTOS et al, 2018). A figura 5 mostra a interação de duas proteínas importantes, cujas expressões podem estar alteradas em pacientes com endometriose.…”
Section: Polimorfismos Genéticos Na Endometrioseunclassified
“…CYP1A1 regulates phase I metabolism of polycyclic aromatic hydrocarbons that can be harmful to the homeostasis of mammal's reproductive system [32]. A large variety of studies have investigated the relationship between CYP1A1 polymorphisms and infertility in Chinese [33][34][35], Brazilian [36], Indian [37], Turkish [38] and German [40] populations. Another risk factor for male infertility is the polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene.…”
Section: Gene Polymorphisms Leading To Male Infertilitymentioning
confidence: 99%